AR‐V7 in circulating tumor cells cluster as a predictive biomarker of abiraterone acetate and enzalutamide treatment in castration‐resistant prostate cancer patients. Issue 8 (5th March 2018) - Okegawa, Takatsugu; Ninomiya, Naoki; Masuda, Kazuki; Nakamura, Yu; Tambo, Mitsuhiro; Nutahara, Kikuo
Abstract : Objective: We examined whether androgen receptor splice variant 7 (AR‐V7) in circulating tumor cell(CTC)clusters can be used to predict survival in patients with bone metastatic castration resistant‐prostate cancer (mCRPC) treated with abiraterone or enzalutamide. Methods: We retrospectively enrolled 98 patients with CRPC on abiraterone or enzalutamide, and investigated the prognostic value of CTC cluster detection (+ v −) and AR‐V7 detection (+ v −) using a CTC cluster detection − based AR‐V7 mRNA assay. We examined ≤50% prostate‐specific antigen (PSA) responses, PSA progression‐free survival (PSA‐PFS), clinical and radiological progression‐free survival (radiologic PSF), and overall survival (OS). We then assessed whether AR‐V7 expression in CTC clusters identified after On‐chip multi‐imaging flow cytometry was related to disease progression and survival after first‐line systemic therapy. Results: All abiraterone‐treated or enzalutamide‐treated patients received prior docetaxel. The median follow‐up was 20.7 (range: 3.0‐37.0) months in the abiraterone and enzalutamide cohorts, respectively. Forty‐nine of the 98 men (50.0%) were CTC cluster (−), 23 of the 98 men (23.5%) were CTC cluster(+)/AR‐V7(−), and 26 of the 98 men (26.5%) were CTC cluster(+)/AR‐V7(+). CTC cluster(+)/AR‐V7(+) patients were more likely to have EOD ≥3 at diagnosis ( P  = 0.003), pain ( P  = 0.023), higher alkaline phosphatase levels ( P  < 0.001), and visceral metastases ( P  < 0.001). On multivariable analysis, pretherapy CTC cluster(+), CTC cluster(+)/AR‐V7(−), and ALP >UNL were independently associated with a poor PSA‐PFS, radiographic PFS, and OS in abiraterone‐treated patients and enzalutamide‐treated patients. Conclusion: The CTC clusters and AR‐V7‐positive CTC clusters detected were important for assessing the response to abiraterone or enzalutamide therapy and for predicting disease outcome.